Direct acting oral anticoagulants for the treatment of suspected heparin‐induced thrombocytopenia. (25th July 2017) - Davis, Kyle A.; Davis, Daphne O.
Abstract: Objective: To evaluate the efficacy and safety of direct oral anticoagulant (DOAC) therapy in hospitalized patients with suspected heparin‐induced thrombocytopenia (HIT). Methods: Retrospective cohort study of adult patients prescribed apixaban, dabigatran, or rivaroxaban for the treatment of acute HIT from January 1, 2013 to January 1, 2017. Eligibility requirements included an intermediate or high pretest probability for HIT (4T score≥4) and a positive IgG‐specific anti‐PF4/heparin complex assay. The primary outcome measure was the composite of newly diagnosed venous or arterial thromboembolism, gangrene, or amputation due to critical limb ischemia during hospitalization. Results: A total of 12 patients were included for analysis, five of which experienced HIT‐related thrombosis prior to initiation of DOAC therapy. Seven patients received parenteral therapy with argatroban prior to initiation of DOAC treatment. Nine patients were treated with apixaban while three received rivaroxaban for an average of 9.33 days while hospitalized. Zero patients experienced the primary outcome of HIT‐related thrombosis, and no patients experienced major bleeding post DOAC initiation. All patients achieved platelet recovery while receiving DOAC therapy. Conclusions: In this small retrospective study of adult patients treated for acute HIT, treatment with DOAC therapy was not associated with in‐hospital thrombotic or hemorrhagic events.